Simulation of seismo-acoustic probing of a heterogeneous layer in an infinite medium - Zaslavsky, Yuriy Mikhailovich; Zaslavsky, Vladislav Yurievich (Computational Continuum Mechanics, 2012)
This paper describes the computation and analysis of acoustic and seismic SH-waves produced by a source of harmonic oscillations located near a heterogeneous layer that differs by wave velocity or density from the host medium. The patterns of spatial distribution of wave amplitude near the source and the layer are plotted. The possibilities of probing the heterogeneity (heterogeneous layer) and of defining the informative signs required for the prognosis of heterogeneity parameters are demonstrated.
Keywords: acoustic field; SH-wave; source of harmonic oscillations; medium; heterogeneity; heterogeneous layer; probing